Conviction as Divine Influence or Human Manipulation: LGBTQ+ Christians and a Harmful Habitus - Jarrard, Clayton (My University, 2020)
Experiencing same-sex attraction can be a devastating situation for a young Christian growing up within a condemning religious community, as it is often seen as sinful and morally wrong. Religious conviction always plays a central role in the difficulty of reconciling faith and an LGBTQ+ identity, since it is accepted to be of divine influence. There is an underlying tension through this piece of whether conviction is of divine or human origin. Using research conducted with LGBTQ+ Christians, this essay offers an examination of religious conviction as a social process. Bourdieu’s concept of the habitus provides a helpful tool in understanding the occurrence of conviction through the learned processes, internalizations, and embodiments of LGBTQ+ Christians as they navigate a Christian social field--structured by fundamental concepts of the human, human nature, and how to live a life of flourishing that are constrained by knowledge-power relations--that rebukes their experience as sinful. By drawing on critiques of the habitus , studies of feeling, emotion, and the processes of assigning these meaning, and ethnographic work in a manipulative Christian setting, this paper questions the purpose for many of the afflictions LGBTQ+ Christians face and illuminates the elaborate, pervasive process involved in LGBTQ+ Christians developing a habitus within Christian social fields that inflicts harm.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, grand prize